Identifying all persons in Wales with type 1 diabetes mellitus using routinely collected linked data. (2018) - Rafferty, James; Akbari, Ashley; Atkinson, Mark D; Bain, Stephen; Luzio, Stephen; Stephens, Jeffery; Owens, David; Thomas, Rebecca
No abstract available